Back Cover: Joint tagging assisted fluctuation nanoscopy enables fast high‐density super‐resolution imaging (J. Biophotonics 9/2018). Issue 9 (6th September 2018) - Zeng, Zhiping; Ma, Jing; Xi, Peng; Xu, Canhua
Abstract : Based on multicolor quantum dots (QDs) labeling, the joint tagging assisted super‐resolution radial fluctuation (JT‐SRRF) nanoscopy achieves high‐fidelity super‐resolution imaging of subcellular microtubules and fast live‐cell parallel tracking of cholera toxin subunit B (CTB) induced lipid clusters spatially distributed below the optical diffraction limit. This method paves the way for fast high‐density parallel tracking, which is especially beneficial for the investigation of the intensive dynamics in live‐cell applications. Further details can be found in the article by Zhiping Zeng, Jing Ma, Peng Xi, and Canhua Xu (e201800020 ). Abstract : Based on multicolor quantum dots (QDs) labeling, the joint tagging assisted super‐resolution radial fluctuation (JT‐SRRF) nanoscopy achieves high‐fidelity super‐resolution imaging of subcellular microtubules and fast live‐cell parallel tracking of cholera toxin subunit B (CTB) induced lipid clusters spatially distributed below the optical diffraction limit. This method paves the way for fast high‐density parallel tracking, which is especially beneficial for the investigation of the intensive dynamics in live‐cell applications. Further details can be found in the article by Zhiping Zeng, Jing Ma, Peng Xi, and Canhua Xu (e201800020 ).